U-shaped association of serum vitamin A concentrations with all-cause mortality in patients with NAFLD: results from the NHANES database prospective cohort study - Li, Hui; Ye, Jiayuan; Dong, Yitian; Kong, Weiliang; Qian, Guoqing; Xie, Yilian (Frontiers in Nutrition, 2024)
Background: Previous studies have demonstrated a significant association between serum vitamin A concentration and non-alcoholic fatty liver disease (NAFLD) development. However, the long-term prognostic implications of serum vitamin A in patients with NAFLD remain underexplored. This study aims to investigate whether there exists a correlation between serum vitamin A concentrations and overall mortality among subjects diagnosed with NAFLD. Methods: To investigate the association between serum vitamin A concentrations and NAFLD outcomes, we conducted prospective cohort studies using data from the 1999-2006 and 2017-2018 National Health and Nutrition Examination Survey (NHANES). We utilized a multivariate Cox regression model to explore the relationship between serum vitamin A levels and all-cause mortality. Survival curves related to serum vitamin A were constructed using the Kaplan-Meier method. Additionally, the restricted cubic splines (RCS) method was applied to examine potential nonlinear relationships between serum vitamin A concentrations and all-cause mortality of NAFLD. Results: Over a median follow-up period of 10.3 years, a total of 1,399 all-cause deaths were recorded. The weighted average concentration of serum vitamin A was 61.48 ± 0.37 μg/dL. After adjusting for potential confounders, a significant U-shaped relationship was identified between serum vitamin A concentrations and the risk of all-cause mortality in NAFLD patients. This relationship was particularly pronounced in men and elderly individuals aged 60 to 85. Conclusion: Our study reveals a significant non-linear relationship between serum vitamin A concentrations and the risk of all-cause mortality in patients with NAFLD. These findings underscore the importance of monitoring and maintaining optimal serum vitamin A levels to potentially improve survival outcomes in NAFLD patients.